2009
DOI: 10.1073/pnas.0809666106
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled biomimetic [2Fe2S]-hydrogenase-based photocatalyst for molecular hydrogen evolution

Abstract: The large-scale production of clean energy is one of the major challenges society is currently facing. Molecular hydrogen is envisaged as a key green fuel for the future, but it becomes a sustainable alternative for classical fuels only if it is also produced in a clean fashion. Here, we report a supramolecular biomimetic approach to form a catalyst that produces molecular hydrogen using light as the energy source. It is composed of an assembly of chromophores to a bis(thiolate)-bridged diiron ([2Fe2S]) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(142 citation statements)
references
References 29 publications
3
137
0
2
Order By: Relevance
“…As compared with those reported in the literature [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] , the durability and activity of the present system are greatly increased; possibly as a result of the stabilization of the components by chitosan confinement leading to consecutive multi-step electron transfer in equilibrium. The importance of the stabilization was also analysed by exchanging chitosan for relatively small and loose aggregates, anionic SDS (0.166 mol l À 1 ) and cationic CTAB (0.055 mol l À 1 , cetyl trimethyl ammonium bromide) micelles 37 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…As compared with those reported in the literature [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] , the durability and activity of the present system are greatly increased; possibly as a result of the stabilization of the components by chitosan confinement leading to consecutive multi-step electron transfer in equilibrium. The importance of the stabilization was also analysed by exchanging chitosan for relatively small and loose aggregates, anionic SDS (0.166 mol l À 1 ) and cationic CTAB (0.055 mol l À 1 , cetyl trimethyl ammonium bromide) micelles 37 .…”
Section: Discussionsupporting
confidence: 53%
“…From a photochemical point of view, the electron transfer is triggered by the absorption of a photon by a photosensitizer [13][14][15][16][17][18][19][20][21][22][23][24][25] . Since the first attempt by Sun and Åkermark 34 to construct an artificial photocatalytic system for H 2 evolution in 2003, a large number of synthetic model complexes have been pursued to mimic the structure and functionality of the diiron subunit of the natural [FeFe]-H 2 ase H-cluster [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] . It is encouraging to see that the catalytic efficiency for H 2 evolution from artificial photocatalytic systems using mimics of the diiron subsite of [FeFe]-H 2 ase as catalysts has been increased from null to more than hundreds or thousands of turnover numbers (TON) under different irradiation conditions.…”
mentioning
confidence: 99%
“…It should be noted here that a direct comparison of turnover numbers is sometimes intricate as it depends on the concentration of the involved components, i.e., WRC, PS and SR. Inspired by the above-mentioned lead structure several groups, e.g., Wang and Sun [61,62], as well as Hammarström [23], Ott [63] and Reek [64] successfully developed a variety of Fe-based WRC, which resulted in catalyst turnover numbers of up to 466 regarding Fe (Scheme 2). An overview of the applied PS is provided in Scheme 3; selected conditions and TONs are listed in Table 1.…”
Section: Overview Of Molecularly-defined Iron Wrcs and The Respectivementioning
confidence: 99%
“…[25][26][27] Recently we also took advantage of the chromophoric character of porphyrins: the assembly of Zn(II)porphyrins onto a functionalised bis (thiolate)-bridged ([2Fe2S]) diiron-based hydrogenase catalyst led to a supramolecular complex that displayed photo-activity forming molecular hydrogen upon exposure to light in the presence of a proton source. 28 Since the supramolecular approach to catalyst exploration is very versatile we aimed at extending the concept to other building blocks. We demonstrated that the pyridyl analogues of classical BIAN-ligands could be used as the template ligand, 29 and we also showed that Zn(II)salphen building blocks can be used analogously to Zn(II)porphyrins.…”
Section: Introductionmentioning
confidence: 99%